1975
DOI: 10.1073/pnas.72.9.3328
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical properties of fractionated chromatin.

Abstract: Sonicated chicken reticulocyte chromatin was fractionated into transcriptionally active and transcriptionally repressed components. The active fraction is 8% of the whole chromatin but contains 70% of the newly synthesized chromosomal RNA. This RNA has five times as many hemoglobin RNA sequences as does the RNA in the repressed fraction. The amount of the active fraction in the chromatins of several tissues correlates with their synthetic activity. The molecular weight of the DNA of the repressed fraction is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The hypothesis that condensed chromatin is usually characterized by very low or no transcriptional activity, and that transcription occurs in loosely packed forms of chromatin (including, in most cells, the nucleolar chromatin) has received support from studies of ultrathin sections in the electron microscope and from the numerous attempts to separate transcriptionally active from inactive chromatin biochemically (for references, see Anderson et al 1975;Berkowitz and Doty 1975;Krieg and Wells 1976;Rickwood and Birnie 1976;Gottesfeld 1977). Electron microscopic autoradiography has revealed that sites of RNA synthesis are enriched in dispersed chromatin regions located at the margins of condensed chromatin (Fakan andBernhard 1971, 1973;Bouteille et al 1974;Bachellerie et al 1975) and are characterized by the occurrence of distinct granular and fibrillar ribonucleoprotein (RNP) structures, such as perichromatin granules and fibrils.…”
mentioning
confidence: 99%
“…The hypothesis that condensed chromatin is usually characterized by very low or no transcriptional activity, and that transcription occurs in loosely packed forms of chromatin (including, in most cells, the nucleolar chromatin) has received support from studies of ultrathin sections in the electron microscope and from the numerous attempts to separate transcriptionally active from inactive chromatin biochemically (for references, see Anderson et al 1975;Berkowitz and Doty 1975;Krieg and Wells 1976;Rickwood and Birnie 1976;Gottesfeld 1977). Electron microscopic autoradiography has revealed that sites of RNA synthesis are enriched in dispersed chromatin regions located at the margins of condensed chromatin (Fakan andBernhard 1971, 1973;Bouteille et al 1974;Bachellerie et al 1975) and are characterized by the occurrence of distinct granular and fibrillar ribonucleoprotein (RNP) structures, such as perichromatin granules and fibrils.…”
mentioning
confidence: 99%
“…There is a large body of data showing that chromatin which is being more actively transcribed has higher ratios of non-histone protein/DNA (16,17,18,191 and lower ratios of histone/DNA [16,18,20,211 and this may account for the higher levels of transcription of the more slowly replicating chromatin DNA. However, the chromatin DNA that replicates more slowly during the first 10 min of S or the last half of S is richer in non-histone chromatin proteins and therefore may have fewer histones than the more rapidly replicating chromatin DNA.…”
Section: Eflect Of Inhibitors Upon Chromatin Synthesismentioning
confidence: 99%
“…However, the chromatin DNA that replicates more slowly during the first 10 min of S or the last half of S is richer in non-histone chromatin proteins and therefore may have fewer histones than the more rapidly replicating chromatin DNA. There is a large body of data showing that chromatin which is being more actively transcribed has higher ratios of non-histone protein/DNA (16,17,18,191 and lower ratios of histone/DNA [16,18,20,211 and this may account for the higher levels of transcription of the more slowly replicating chromatin DNA.…”
Section: Eflect Of Inhibitors Upon Chromatin Synthesismentioning
confidence: 99%
“…It is noteworthy that not only chromatin fractions that are disperse and active in transcription but also those that are condensed and inactive in transcription, contain RNA species (Berkowitz & Doty, 1975;Gottesfeld et al, 1975). In some cases the amount of heterochromatin-associated RNA is even higher than that of RNA associated with euchromatin (Paul & Duerksen, 1975).…”
mentioning
confidence: 99%